Pd-catalyzed oxidative kinetic resolution of 2-azido-1-arylethanols - Sayyed, I. A.; Kumar, N. S. C. R.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
(-)-Sparteine/Pd (II) complex in combination with oxygen as a stoichiometric oxidant, catalyses the oxidative kinetic resolution of P-azido alcohols to afford the corresponding chiral 2-azido-1-arylethanols.
Keywords: (-)-sparteine-Pd (II) complex; beta-azidoalcohol; chiral 2-azido-1-arylethanol; Kinetic resolution